2015
DOI: 10.1152/ajprenal.00022.2014
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle contrast imaging reveals large-scale synchronization of cortical autoregulation dynamics influenced by nitric oxide

Abstract: Mitrou N, Scully CG, Braam B, Chon KH, Cupples WA. Laser speckle contrast imaging reveals large-scale synchronization of cortical autoregulation dynamics influenced by nitric oxide. Am J Physiol Renal Physiol 308: F661-F670, 2015. First published January 13, 2015; doi:10.1152/ajprenal.00022.2014.-Synchronization of tubuloglomerular feedback (TGF) dynamics in nephrons that share a cortical radial artery is well known. It is less clear whether synchronization extends beyond a single cortical radial artery or whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 54 publications
1
36
1
Order By: Relevance
“…Previously, we, and others, reported that autoregulation dynamics are synchronized on the surface of the kidney (9,23,39,45). Simulation studies suggest that networks of arterioles would provide smoothing of blood flow in space and time (18,58), which suggests synchronization may contribute to the efficacy of autoregulation.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previously, we, and others, reported that autoregulation dynamics are synchronized on the surface of the kidney (9,23,39,45). Simulation studies suggest that networks of arterioles would provide smoothing of blood flow in space and time (18,58), which suggests synchronization may contribute to the efficacy of autoregulation.…”
Section: Discussionmentioning
confidence: 74%
“…Previously, we, and others, reported large-scale synchronization of renal autoregulation dynamics in renal surface perfusion (9,23,39,45) and suggested that it is mediated by communication among vascular branches via gap junctions (9,39). Furthermore, previous results suggest synchronized autoregulation dynamics contribute to the effectiveness of autoregulation (18,58).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Data were used from a previously published report that probed a different question [25]. All experiments were approved by the Animal Care Committee of Simon Fraser University, in accordance with the guidelines of the Canadian Council of Animal Care.…”
Section: Experimental Data Collectionmentioning
confidence: 99%